Marketing for Small Business Escape Rooms and the Importance of Experiential Learning - Brubaker, Ken; Rawraway, René; McMaster, Abigail G. (Journal of Marketing Development and Competitiveness, 2024)
A semi-rural Ohio escape room collaborated with a local university for an experiential learning initiative, aiming to attract more college students, retain current customers, and enhance marketing strategies. Two questionnaires were employed: one targeting college students and the other existing customers. Findings revealed a higher attendance of upperclassmen students at the escape room and email as the preferred mode of communication. Moreover, a significant correlation between escape room experience, games, food, drinks, and overall satisfaction was observed. The customer-focused survey indicated the primary demographic as individuals aged eighteen to twenty-nine, with a high satisfaction rate of ninety-seven and a half percent. Additionally, sixty-three percent expressed interest in returning for a new escape room design.